Dynamics Of Considerations In The Constitutional Court's Decision In Deciding On The Settlement Of Disputes In The 2024 General Election Of Regional Heads And Deputy Regional Heads Of Serang Regency - Endang Maulana; Mas Iman Kusnandar; Firdaus Firdaus (Universitas Dharmawangsa Medan, 2025)
General Election Result Dispute is a Vote Result Dispute that is the authority of the Constitutional Court, but in several decisions of the Constitutional Court in the Settlement of Regional Head Disputes not only questioned the difference in election results, but also examined and assessed the administrative process of the election stages, to cancel the vote results, which resulted in the cancellation of the general election results. This raises the dialectic of the competence of the Constitutional Court in examining and deciding on the Election Result Dispute case as follows: First, How is the Scope of the Conception of the Election Result Dispute for Regional Heads and Deputy Regional Heads reviewed in the Constitutional Court decision No. 70 / PHPU.BUP-XXIII / 2025?, Second, How is the Constitutional Court Authorized to Examine and Assess Administrative Violations of the General Election Stage Process in Deciding on the Settlement of the General Election Result Dispute for Regent and Deputy Regent?. This study uses the theory of Pragmatic Legal Realism which emphasizes the active role of judges in upholding substantive justice, as well as the Election Theory which places elections as an instrument of democracy that must guarantee the principles of justice, representation, and people's sovereignty. This type of research is descriptive. The analysis method of this research is normative juridical. Data collection techniques are carried out using field studies and literature studies.